Implementation of evidence-based practice in clinical decision-making among midwives working in Central and South Gondar Zone public Hospitals, Ethiopia - Eden Bishaw Taye; Haymanot Alem Muche; Tsion Tadesse Haile; Banchlay Addis; Mihretie Kibret Awoke; Melkie Mekonnen Bekele; Marta Berta Abadi; Zewdu Wasie Taye (Elsevier, 2024)
Background: The incorporation of evidence-based practice into midwifery care improves patient outcomes and quality of care by increasing patient satisfaction, patient safety, and shorter hospital stays. So, the purpose of this study is to assess midwives' implementation of evidence-based practice and the factors associated with it. Method: A cross-sectional study was conducted with 384 randomly selected midwives. Data were collected using a structured, self-administered questionnaire. The collected data was entered into Epi Data version 3.1 and exported to STATA version 17 for analysis. Bivariable and multivariable linear regression models were used to identify factors associated with EBP implementation. Result: The mean EBP implementation score was 32.05 with SD ± 10.52 points out of a possible 70 points, and 199 (51.82 %) of respondents scored above the mean. The factors found to be significantly and independently associated with EBP implementation were level of hospital (primary) [β: 4.12; 95 % CI (2.03, 6.18)], attending continuous professional development [β: 2.36; 95 % CI (0.13, 4.59)], internet access in the hospital [β: 3.68; 95 % CI (1.58, 5.79)], participating in conferences for the last 12 months [β: 4.94; 95 % CI (1.46, 8.41)], and participating in seminars for the last 12 months [β: 4.99; 95 % CI (1.54, 8.43)]. Conclusion: The findings have indicated that nearly half of the study participants had good implementation of evidence-based practice. Level of hospital, attending continuous professional development, internet access in the hospital, participating in conferences for the last 12 months, and participating in seminars for the last 12 months significantly increased the mean overall implementation of evidence-based practice among midwives.